POLARISASI AKSES KE LAYANAN KESEHATAN BERDASARKAN POLA SOSIAL-EKONOMI DAN GEOGRAFI DI KOTA BEKASI - Raihan Arifin, Mochamad; Rohman Syah, Raihan; Audrey, Michella; Laurent Claudia, Sophia; Widiawati, Lutfa; Yunita Mustikawati, Dwi; Handawati, Rayuna (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2025)
Health is a basic human right, but access to health services in Bekasi City still experiences inequality based on socio-economic and geographical factors. This study analyzes inequality in access to health services in Bekasi City based on the distribution of hospitals, population density, and transportation infrastructure. Using a descriptive qualitative method with GIS spatial analysis, this study found that although the number of hospitals is quite large, their distribution is uneven, especially in sub-districts with high population density such as Jatisampurna and Bantargebang, and limited access to public transportation in some areas. These results suggest that there is a need to improve the distribution of health facilities and transportation infrastructure to increase access to health services in Bekasi City